Al-Khayr, Muhammad Abu al-Layth. “The Historical Roots of Fabrications (Waḍiʿ) in Hadith,” Year 4, Issue 16 (Spring 1419 AH/ 1999 CE), Pp. 7-45. - آبادي محمد أبو الليث (Al-Fikr al-islāmī al-muʿāṣir (previously Islamiyat al-Ma’rifah), 1999)
Muhammad Abu al-Layth al-Khayr provides a survey of certain books of history, peoples, fabricated hadiths, sects, groups, and the sciences of hadith to explore the causes of fabrications in hadith (al-waḍiʿ fī al-ḥadīth) and their historical roots. He blames the fabrications on intentional purposes such as: retribution against Islam and Muslims by stricken nations of Jews and Christians; in support of factional parties and political desires; sectarian and doctrinal differences; in support of doctrinal sects such as the Qadariyyah and Jabariyyah; alienation away from Islam at the hands of heretics and atheists; prejudice on the basis of sex or origin; a desire for reform and incentives for asceticism; in support of fiqh schools; and other supporting causes such as not documenting and recording hadiths, the spread of Companions of the Prophet to newly conquered lands, laxity in dealing with fabricators, and the errors of hadith transmitters by delusion or forgetfulness.